ANALYSIS OF ALTERNATIVE DISPUTE RESOLUTION OF DAMAGES ON MURABAHAH FINANCING: (STUDY OF CASE RULING NUMBER 123/PDT.G/2022/PTA.SMG) - Sari, Bunga Lidia; Khutub, Muhammad; Zulhuda, Sonny (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2024)
The development of sharia financing is very important in the context of the needs of the Indonesian people, this financing involves various available contracts, one of which is murabahah contract financing, murabahah contract financing is becoming a common option that is increasingly in demand by the Indonesian people in a fast and easy way, namely by taking a profit margin. The impact of problematic murabahah financing on sharia banking itself is usually related to liquidation conditions, solvency, profitability and probability. This article aims to understand the legal basis and considerations of judges in deciding the murabahah contract in decision number 123/Pdt.G/2022/PTA.Smg as well as knowing the perspective of the compilation of sharia economic law in decision number 123/Pdt.G/2022/PTA.Smg. This article was prepared using a qualitative method which is supported by decision number 123/Pdt.G/2022/PTA.Smg. The conclusion in this article is that a very important consequence of non-fulfillment of default is that creditors can ask for compensation for the costs, losses and interest they suffer. For there to be an obligation to compensate debtors, the law determines that the debtor system. This awareness will function as a binding force for the parties to fulfill the promises they have agreed to. In this way, an agreement can function to prevent broken promises or default. Awareness of the importance of an agreement.